Challenges Faced by Psychiatry Trainees During Residency in Pakistan - Muhammad Asif Kamal, Shafqat Huma, Muhammad Fahim Qasim, Fatima Aamir Khan, Nadia Naveen, Zulfiqar Ali Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Medical students and trainees have higher levels of stress and burnout compared with the general population. Objective: The main objective of this study is to find the challenges faced by psychiatry trainees during residency in Pakistan. Material and methods: This cross sectional study was conducted in Wah medical college / POF hospital Wah Cantt during 2021 to 2022.The data was collected from 100 participants through Snowball technique. Trainees from Pakistan who have completed their residency program or have cleared their exam in last 3 years were included in the study. Results: The data was collected from 100 participants. Among those 100 participants 48 (47.1%) females and 52 (52.9%) males. They rate their trainings in terms of learning as 14.3% participants were considered excellent. Among the 100 trainees who filled the questionnaire, the results showed that majority of the trainees were satisfied with their supervisor in terms of knowledge, competency and willingness to teach. Practical implications: After reading this article we can easily find the problems faced by trainees during the training process. Conclusion: It is concluded that the trainees were satisfied on the whole with the supervisors knowledge, competency and the layout of the training program. Keywords: Satisfaction, Trainees, Programmed, Residency, Psychiatric